2020
DOI: 10.3390/pharmaceutics12121193
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Resistance to Chemotherapy in Breast Cancer and Possible Targets in Drug Delivery Systems

Abstract: Breast cancer (BC) is one of the most important cancers worldwide, and usually, chemotherapy can be used in an integrative approach. Usually, chemotherapy treatment is performed in association with surgery, radiation or hormone therapy, providing an increased outcome to patients. However, tumors can develop resistance to different drugs, progressing for a more aggressive phenotype. In this scenario, the use of nanocarriers could help to defeat tumor cell resistance, providing a new therapeutic perspective for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 87 publications
1
28
0
Order By: Relevance
“…We showed that a shorter TTF (less than 183 days) was significantly associated with poorer OS than that of patients with a longer TTF, suggesting that the short-term response to first-line treatment might be associated with poorer OS. Tumor chemoresistance is associated with low efficacy of chemotherapy 16 , 17 and might be one of the main causes of short-term response to first-line treatment in this study. For example, a multidrug resistance system that surviving tumor cells acquire after chemotherapy treatment promotes the efflux of anticancer drugs from tumor cells, reducing drug absorption 17 .…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…We showed that a shorter TTF (less than 183 days) was significantly associated with poorer OS than that of patients with a longer TTF, suggesting that the short-term response to first-line treatment might be associated with poorer OS. Tumor chemoresistance is associated with low efficacy of chemotherapy 16 , 17 and might be one of the main causes of short-term response to first-line treatment in this study. For example, a multidrug resistance system that surviving tumor cells acquire after chemotherapy treatment promotes the efflux of anticancer drugs from tumor cells, reducing drug absorption 17 .…”
Section: Discussionmentioning
confidence: 76%
“…Tumor chemoresistance is associated with low efficacy of chemotherapy 16 , 17 and might be one of the main causes of short-term response to first-line treatment in this study. For example, a multidrug resistance system that surviving tumor cells acquire after chemotherapy treatment promotes the efflux of anticancer drugs from tumor cells, reducing drug absorption 17 . In addition, tumor chemoresistance can be associated with various mechanisms including interactions among cancer cells and the tumor microenvironment 16 , 17 .…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“… Daunorubicin IL-3 IL-3 can induce ERK pathway. ERK/Mcl-1 pathway can inhibit BCL2 protein activity, and lead to drug resistance [ 94 ] Cyclophosphamide IL-6 IL6 can induce drug resistance via JAK/STAT3 and NF-kappaB IL6-dependent pathway [ 95 ] Taxotere IL-8 IL-8 can induce drug resistance and cancer progression, through PLC-PKC, PI3K-AKT, Rho-GTPase family, FAK/Src and MAPK cascade signals and NF-κB pathway [ 96 ] Methyl methane sulfonate TGF-β TGF-β can induce drug resistance through miR21 expression and subsequent suppression of MSH2 mRNA production [ 97 ] 5-Fluorouracil OSM* OSMRs/JAK1/STAT3 axis contributes to the resistance to the targeted drugs in cancer cells [ 95 , 98 ] Methotrexate IL-17 IL-17 leads to the production of KEAP1-Nrf2 and NF-KB transcription factors, through PI3K/AKT/mTOR pathway; it can induce drug resistance by expressing the BCRP molecule [ 99 , 100 ] Etoposide IL-11 IL-11 induces resistance to chemotherapy drugs, through gp130/JAK/STAT3/Bcl2 pathway [ 101 ] Oxaliplatin CXCL1 Drug resistance is induced via CXC-Chemokine/NF-κB signaling pathway [ 102 ] Abbreviation: IL interleukin, ERK extracellular signal-regulated kinase, Mcl-1 myeloid cell leukemia 1, Bax Bcl-2-associated X protein, JAK Janus kinase, STAT signal transducer and activator of transcription 3, NF-Kβ nuclear factor-kβ, PLC phospholipase C, PKC protein kinase C, PI3K phosphoinositide 3-kinase, Akt serine threonine kinase, ...…”
Section: Discussionmentioning
confidence: 99%
“…These tiny secondary tumors may only be treated therapeutically on a systemic basis while also acknowledging common resistance mechanisms [ 6 ]. Drug biodistribution by the cardio-vascular system and drug extravasation/permeation into tissue microenvironment are key factors in delivering chemotherapeutic or immunotherapeutic drugs to cancer cells inside tumors.…”
Section: Introductionmentioning
confidence: 99%